Mucosal microbiome of surgically treated terminal ileal Crohn’s disease - Loch, Florian N.; Kamphues, Carsten; Menzel, Peter; Schwarzer, Rolf; Beyer, Katharina; Schineis, Christian (Frontiers in Cellular and Infection Microbiology, 2024)
Crohn's disease (CD) is accompanied by changes in the microbiome. The role of these changes, as well as their precise association with disease course and activity, remain ambiguous. In this prospective single-center study, the mucosal microbiome of surgical CD and non-CD patients was compared at the time of surgery. Microbial analyses were individually performed for ileal and colonic tissue samples obtained during surgery, using 16S-rRNA-gene amplicon sequencing. Three groups out of 46 included patients were formed: 1) a study group of CD patients receiving ileocecal resection due to CD affection (CD study, n=10), 2) a control group of non-CD patients receiving intestinal resections due to indications other than CD (non-CD control, n=27), and 3) a second control group of CD patients with resection of intestine not affected by CD (CD non-affected control, n=9). Alpha-and Shannon diversity were not different between all formed groups and analyzed regions (p>0.05). Several significant taxonomic differences were seen at phylum-, order-, and genuslevel between the formed groups, such as a decrease of Firmicutes (phylum-level) and an increase of Bacteroides and Escherichia/Shigella/Pseudescheria (genus-level) in CD studycolon vs. non-CD controlcolon (p≤0.05). CD non-affected control presented the largest amount of differently abundant taxa in comparison to the others groups. These results underline that CD is accompanied by changes in affected and non-affected intestinal regions compared to non-CD controls. This study contributes the mucosal microbiome of a well-defined subset of surgical CD patients without confounding aspects of fecal microbiome and regional microbial differences to existing literature.